Notes on parasitoid assemblage reared from larvae of legume pod borers Maruca vitrata (Fabricius) and Etiella zinckenella Treitschke - Long, Khuat Dang; Hoa, Dang Thi (Academia Journal of Biology, 2012)
Nine larval parasitoids were reared from two important pests infesting legume crops, the legume pod borers Maruca vitrata and Etiella zinckenella. Five parasitoids were reared from M. vitrata larvae: Sinophorus sp., Therophilus javanus (Bhat & Gupta), Therophilus marucae van Achterberg & Long, Therophilus robustus van Achterberg & Long and Trathala flavoorbitalis (Cameron); another five parasitoids were reared from E. zinckenella larvae: Apanteles hanoii Tobias & Long, Apanteles taragamae Viereck, Bracon sp., Trathala flavoorbitalis (Cameron) and Tropobracon luteus Cameron. Morphological characters of the parasitoids are provided. Among larval parasitoids of two legume pod borers, the ichneumonid wasp Trathala flavoorbitalis is considered to be a common parasitoid from larvae of both borers, this ichneumonid parasitoid was previously reared from the leaf folders Omiodes indica, Cnaphalocrocis medinalis and the corn borer Ostrinia furnacalis, the braconid parasotoid Tropobracon luteus is newly reared from larvae of E. zinckenella, this braconid parasitoid was previously recorded from the rice stem borers Chilo suppressalis, Scirpophaga incertulas and Sesamia infferens.